'It's good to have the knowledge and the confidence': Mental health student nurses' views of a medication workshop. (13th May 2022) - Goodwin, John; White, Sheila; O'Malley, Maria; Hurley, Emma; O'Donovan, Aine; Kelly, Peter
ABSTRACT: The administration of medication in a safe manner is a key nursing role and nursing regulatory bodies mandate that it is part of undergraduate training. However, it has been noted that qualified nursing staff are dissatisfied with the knowledge demonstrated by students. As such, a 2‐day evidence‐based workshop on medication management for final‐year nursing students was facilitated to address knowledge deficits. Content was delivered by academics and practicing nurses. The aims of this study were to evaluate internship mental health student nurses' experiences of a 2‐day medication management workshop. A qualitative descriptive design was adopted. Three focus group interviews were held with student nurses who partook in the workshop. Data were analysed using reflexive thematic analysis. Three themes were identified: Developing Confidence around Medication Management, Reflections on Learning Gained from the Workshop, and Enhancing Awareness and Vigilance of Medication Errors. Overall, participation in the workshop was identified as having a positive impact on students' knowledge, competence, and confidence in relation to becoming a safe practitioner. Students reported that the timing of the workshop – during internship – was appropriate for their knowledge needs. Findings indicate that the right amount of information was delivered by the right people, at the right time, in the right way. This study has highlighted the positive impact of a 2‐day workshop delivered in the final year of mental health student nurse training, on their confidence and competence in the area of medication management. It provides some insight into how a practical collaborative approach to this type of education between academics and clinicians can help students bridge the theory–practice gap.